Systematic Review of the Impact of Transcranial Direct Current Stimulation on the Neuromechanical Management of Foot and Ankle Physical Performance in Healthy Adults - Xiao, Songlin; Wang, Baofeng; Zhang, Xini; Zhou, Junhong; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: This study aims to review existing literature regarding the effects of transcranial direct current stimulation (tDCS) on the physical performances of the foot and ankle of healthy adults and discuss the underlying neurophysiological mechanism through which cortical activities influence the neuromechanical management of the physical performances of the foot and ankle. Methods: This systematic review has followed the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses. A systematic search was performed on PubMed, EBSCO, and Web of Science. Studies were included according to the Participants, Intervention, Comparison, Outcomes, and Setting inclusion strategy. The risk of bias was assessed through the Cochrane Collaboration tool, and the quality of each study was evaluated through the Physiotherapy Evidence Database (PEDro) scale. Results: The electronic search resulted in 145 studies. Only eight studies were included after screening. The studies performed well in terms of allocation, blinding effectiveness, and selective reporting. Besides, the PEDro scores of all the studies were over 6, which indicated that the included studies have high quality. Seven studies reported that tDCS induced remarkable improvements in the physical performances of the foot and ankle, including foot sole vibratory and tactile threshold, toe pinch force, ankle choice reaction time, accuracy index of ankle tracking, and ankle range of motion, compared with sham. Conclusion: The results in these studies demonstrate that tDCS is promising in improving the physical performances of the foot and ankle. The possible underlying mechanisms are that tDCS can ultimately influence the neural circuitry responsible for the neuromechanical regulation of the foot and ankle and then improve their physical performances. However, the number of studies included was limited and their sample sizes were small; therefore, more researches are highly needed to confirm the findings of the current studies and explore the underlying neuromechanical effects of tDCS.